Análisis del biotipo de pacientes comprendidos entre 15 a 30 años utilizando el método de Vert Ricketts en el periodo octubre 2017-mayo 2018. - Cañar Mora, Kelvin Alexander (2018)
Facial biotypes determine morphological, functional, craniofacial and occlusal characteristics of the stomatognathic system, have value in the diagnosis and treatment plan of various craniofacial and dental discrepancies and allow to predict the direction of maxillofacial growth. Among the most used cephalometric methods for the determination of the facial biotype we find the Ricketts Vert method. We analyzed 30 cephalometric radiographs of patients between 15 and 30 years old of the private clinic “Dental Estetic” of the city of Loja, with the objective of determining which is the most frequent facial biotype through Vert cephalometric analysis of Ricketts, the tracings were made manually and their data were processed in the program Microsoft Excel, obtaining as results that the majority of patients were of the mesofacial type with 30%, followed by the brachyfacial and soft dolichofacial type with 20%, dolichofacial with 13.3%, severe dolichofacial and severe brachyfacial with 3.3%. It was determined that the most predominant facial biotype in relation to sex was the same, in the male corresponding to the mesofacial biotype with 30.33% and 23.5% in women. The greater variation of the angles measured in relation to the general rule according to Vert of Ricketts was of the mandibular arch with 29%. By means of the analysis cephalometric it is verified that the method of vert of Ricketts confirms the importance of determining the facial biotype, facilitating the approach of the treatment and prognosis of the same one. Keywords: cephalometric analysis, Ricketts the vert the method, facial biotype,